Diversifikasi Pangan Olahan Buah Kurma Ajwa (Phoenix dactylifera L.) sebagai Bahan Kombinasi Produk Minuman Cokelat Bermineral - Shabrina Dini Alifah Salwa; Iswendi Iswendi (MASALIQ, 2025)
Phoenix dactylifera L. is widely available on the market and is generally consumed directly, whereas kurma Ajwa dates have a high nutritional content (water 22.8 g; ash 3.43 g; protein 2.91 g; fat 0.47 g; carbohydrates 70%; dietary fiber 6.5–11.5%; and mineral contents of sodium 7.5 mg/100 g, magnesium 150 mg/100 g, calcium 187 mg/100 g, potassium 476.3 mg/100 g, phosphorus 27 mg/100 g, iron 0.15 mg/100 g, and zinc 0.52 mg/100 g), thus presenting potential as a food source to support the prevention of nutritional problems such as stunting. This study aimed to analyze the effect of adding Ajwa date pulp juice as a form of food diversification on the aroma, color, taste, texture, and mineral content of a chocolate beverage. A quantitative method was employed with varying concentrations of Ajwa date pulp addition of 0 g (control), 5 g, 10 g, 15 g, 20 g, and 25 g, coded as M1 to M6, respectively. The characteristics of the chocolate date beverage were evaluated using a hedonic test for aroma, color, taste, and texture, while the nutritional value (minerals) was analyzed by XRF in the sample most preferred by the panelists. Data were statistically analyzed using one-way ANOVA. The results show that the inclusion of Ajwa date pulp juice in the chocolate beverage formulation received positive panelist preferences and tended to increase nutritional value, particularly mineral content; M6 was the most preferred product among 25 panelists, and one of the minerals that increased was calcium, from 41.77 in M1 to 42.172 in M6. However, the addition of Ajwa date pulp juice at different concentrations did not produce statistically significant effects on the hedonic test results (aroma, color, taste, and texture) or on the mineral content of the beverage. Thus, varying levels of Ajwa date pulp juice in chocolate beverages can increase mineral levels, although not significantly in statistical terms, and have potential to be utilized as an alternative form of chocolate beverage diversification based on functional foods.